Management of Palm Oil by the Government of the Republic of Indonesia - SALEH, CHOIRUL; HARDIWINATA, WAWAN H.; MINDARTI, LELY INDAH; ZAUHAR, SOESILO (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Sustainable palm oil governance in Indonesia becomes part of the work governance perspective. This type of research is a qualitative one, historical patterned with descriptive analysis. Data collection methods used are observation, interviews, and documentation. Data analysis was performed by using the model of Miles, Huberman, and Saldana consisting of four activities, namely combining data, condensing data, displaying data, and gathering conclusions and verification. There are many actors involved in the implementation of indonesian sustainable palm oil. Local people who agree with the law can accept or reject the development of oil palm on the land they claim.RESUMEN La gobernanza sostenible del aceite de palma en Indonesia forma parte de la perspectiva de la gobernanza laboral. Este tipo de investigación es una investigación cualitativa, histórico-modelada con análisis descriptivo. Los métodos de recopilación de datos utilizados son la observación, las entrevistas y la documentación. El análisis de los datos se ejecutó utilizando el modelo de Miles, Huberman y Saldana el cual consta de cuatro actividades, a saber, combinar datos, condensar datos, mostrar datos y recopilar conclusiones / verificación. Hay muchos actores involucrados en la implementación del aceite de palma sostenible de Indonesia. La población local que esté de acuerdo con la ley puede aceptar o rechazar el desarrollo de la palma aceitera en la tierra que reclaman.